2016
DOI: 10.1371/journal.pone.0149318
|View full text |Cite
|
Sign up to set email alerts
|

Tubo-Ovarian Abscess (with/without Pseudotumor Area) Mimicking Ovarian Malignancy: Role of Diffusion-Weighted MR Imaging with Apparent Diffusion Coefficient Values

Abstract: ObjectiveTo assess the added value of diffusion-weighted magnetic resonance imaging (DWI) with apparent diffusion coefficient (ADC) values compared to MRI, for characterizing the tubo-ovarian abscesses (TOA) mimicking ovarian malignancy.Materials and MethodsPatients with TOA (or ovarian abscess alone; n = 34) or ovarian malignancy (n = 35) who underwent DWI and MRI were retrospectively reviewed. The signal intensity of cystic and solid component of TOAs and ovarian malignant tumors on DWI and the corresponding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 26 publications
(35 reference statements)
2
12
0
Order By: Relevance
“…However, the rest of the benign lesions (which was 1.97 ± 0.428 after the exclusion of the TOAs) showed no significant difference from that of the borderline (1.83 +/− 0.27) or the invasive malignant tumors (2.1 +/− 0.44). This agrees with a study conducted by Wang et al [12] on 69 patients (34 patient with TOA for characterizing the TOA mimicking ovarian malignancy); it showed that the mean ADC value of TOA cystic component was lower than that in malignant tumors (1.04 ± 0 0.41 × 10 −3 mm 2 /s vs. 2.42 ± 0.38 × 10 −3 mm 2 /s; P < 0.001).…”
Section: Discussionsupporting
confidence: 92%
“…However, the rest of the benign lesions (which was 1.97 ± 0.428 after the exclusion of the TOAs) showed no significant difference from that of the borderline (1.83 +/− 0.27) or the invasive malignant tumors (2.1 +/− 0.44). This agrees with a study conducted by Wang et al [12] on 69 patients (34 patient with TOA for characterizing the TOA mimicking ovarian malignancy); it showed that the mean ADC value of TOA cystic component was lower than that in malignant tumors (1.04 ± 0 0.41 × 10 −3 mm 2 /s vs. 2.42 ± 0.38 × 10 −3 mm 2 /s; P < 0.001).…”
Section: Discussionsupporting
confidence: 92%
“…Morphological MRI usually shows a complex cystic mass with ill-defined borders, thickened walls, and thickened septa, with low SI on T1W images and heterogeneously high SI on T2W images, which enhance after gadolinium-based contrast administration ( Figure 4 ). As can be seen in Figure 4 , the cystic component can present with low to slightly high SI on T1W images and slightly low to high SI on T2W images ( 26 , 27 , 32 , 38 ) . There are studies-such as those conducted by Li et al.…”
Section: Tubo-ovarian Abscessmentioning
confidence: 88%
“…Tubo-ovarian abscess is a condition within the wide spectrum of pelvic inflammatory disease ( 26 , 32 , 38 ) . Morphological MRI usually shows a complex cystic mass with ill-defined borders, thickened walls, and thickened septa, with low SI on T1W images and heterogeneously high SI on T2W images, which enhance after gadolinium-based contrast administration ( Figure 4 ).…”
Section: Tubo-ovarian Abscessmentioning
confidence: 99%
“…Sensitivity (100 vs. 47%), specificity (97 vs. 91%), positive predictive value (97 vs. 84%), negative predictive value (100 vs. 64%), and accuracy (99 vs. 70%) are all improved with DWI compared with MRI without DWI. 54 Similarly, in another study, sensitivity and negative predictive value for diagnosis of pelvic inflammatory disease on MRI increased with the addition of DWI, from 90.7 and 70.0% to 98.4 and 93.3%, respectively. 55…”
Section: Acute Pelvic Pain: Uterine and Adnexal Pathologymentioning
confidence: 83%
“…TOA and ovarian neoplasm may appear similar on imaging, as both entities can have thickened enhancing septa, thick mucin-like fluid, and be associated with lymphadenopathy. 54 The use of DWI can be especially helpful to distinguish a simple ovarian cystic lesion or hydrosalpinx from TOAs and pyosalpinx. In the appropriate clinical setting, the presence of a cystic lesion with restricted diffusion is highly suspicious for TOA, whereas a simple cyst or hydrosalpinx will not restrict diffusion.…”
Section: Acute Pelvic Pain: Uterine and Adnexal Pathologymentioning
confidence: 99%